Praktek Suluk pada Ajaran Tarekat Naqshabandiyah Tahun 1905-2020 di Sumatera Barat (Studi Kasus: Kota Padang Tahun 1905-2020) - Ade Selvia; Elfita` Yulianti; Feldisa Sekar` Wulandari; Muhammad Arif Fadhilah (Medan Resource Center, 2022)
This research has a background that discusses the transformation of suluk practices in the Naqsabandiyah tariqa from 1905-2020. The cause of the transformation is due to the difference in understanding between young and old people and the current conditions in which followers are lulled by worldly affairs. The formulation of the problem developed in this article is how the transformation of suluk practice in the teachings of the Naqsabandiyah tariqa from 1905-2020 AD. The purpose of the study is to find out how the Suluk Practice Changes in the Teachings of the Naqshabandiyah Order, both from the way of remembrance, the books studied, and so on. The methodology used in this study uses historical research methods, including heuristics, verification, interpretation, and historiography. Using the auxiliary sciences of sociology; Changes can occur along with the development of time and times, many factors underlie changes in the practice of the Suluk Tarekat Naqsabandiyah; This research uses historical methods. Heuristics, collecting primary sources accessed from the British Library. Secondary sources are relevant on this topic, mostly from books, scientific articles, and theses. Verification is carried out by sorting only those sources that are declared to have used the scientific method. Interpretation is carried out by conducting analysis and synthesis with a social approach; The practice of Suluk can change due to several factors, including from the teacher or Murshid himself. Differences in perception of each individual will be inevitable. In the 19th century, books and books for the guidance of the Naqshabandiyah Order still came from sheikhs in the Middle East, while in the 20th century, the books used have been modified from the writings of sheikhs andteachers in Nusantara. Furthermore, the practice of suluk in West Sumatra, especially in Surau Baitul Makmur in Pauh has been modified and shortened to 3 days because it considers how busy human activities were in the 2000s